THE INFLUENCE OF ISLAMIC COMMERCIAL BANK’S LETTER OF CREDIT FINANCING AND EXCHANGE RATE TOWARDS INDONESIA'S EXPORTS FROM 2014 TO 2018 - Andi Triyawan; Amalia Syafira Novitasari (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2020)
International trade activities become one of the important factors in economic growth. Compared to the implementation of domestic trade, international trade is much more complex. Thus, it is certain that both will be in trouble paying if the buyer has no foreign exchange (means of payment). Based on the above background the researcher presents financing through Islamic Commercial Banks. Besides, it is supported by additional economic variables named the exchange rate. The method used descriptive quantitative with secondary data collection techniques scattered on Central Statistics Agency (BPS) reports, Bank Indonesia (BI), and Financial Services Authority (OJK). The data analysis technique is Multiple Linear Regression based on OLS (Ordinary Least Square). The results of this research, that 1) Islamic Commercial Bank Letter of Credit (L/C) financing influnced exports by 10% and 90% influenced by other variables 2) Exchange rates influenced of 2% and the remaining 98% influenced by other variables 3) Letter of Credit (L/C) Financing Islamic Commercial Banks and foreign exchange rates can explain their influenced on export value by 21% while the remaining 79% are influenced by other variables.